Evolution of Mortality in Lung and Bronchi Cancer in the South Health Region of the State of Mato Grosso, 2010 – 2019 (Research, Society and Development, 2022)
Objective: To carry out a survey of data on the mortality rate associated with lung and bronchial cancer in the municipalities of the Southern Health Region of the State of Mato Grosso. Methodology: This is a descriptive, retrospective time series study, in which data were obtained on the number of deaths from malignant neoplasms of the bronchi and lungs in people living in the Southern Health Region of Mato Grosso, between 2010 and 2019, through the Mortality Information System (SIM), made available by the Department of Informatics of the Unified Health System (DATASUS). The mortality rate for the municipalities was calculated by the ratio between the total number of deaths from bronchial or lung cancer and the population estimate, stratified by sex and age, each year. The direct method was used to standardize mortality rates by age group. Results and Discussion: From the available data, it was found that 12.49% of deaths caused by cancer in the 19 municipalities in the region were due to bronchial or lung cancer. Mortality was higher in men (12.07 deaths/100 thousand) than in women (7.70 deaths/100 thousand). Furthermore, people aged between 70 and 79 years had a higher mortality rate (104.05 deaths/100 thousand) than those in the younger age groups. This shows that both findings agree with the literature. Conclusion: The data demonstrate a higher mortality associated with males, as well as with older age, which agrees with the literature.